Tashmim Mawad Ta'limiyah li Tanmiyah Maharah Al-Kalam bi Jami'ah Dar As-Salam Gontor - Lubis, Rahmat Hidayat; Fikriyah, Fikriyah; Nurahmah, Riska Hanan; Hasanah, Qudwatun; Norsalim, Khairunnisa Binti Mohd (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2023)
This study aims to describe the specifications and efficiency of educational materials for improving the speaking abilities of Language Preparation Program participants at the University of Darussalam Gontor. Research and development were used in the study, and interviews, identification, testing, and written documentation were used as data collection techniques. The research utilized the test-paired t-formula to analyze the data. The results of this research led to the production of instructional materials that include explanations of difficult words and engaging language training, as well as dialogue and conversation tools that are appropriate for their clientele, with added graphics and color. The results of this study also showed that participants' linguistic competency improved after using specified materials, especially in terms of their speech abilities, as shown by the fact that the post-test scores in the enlarged experiment were higher than the pre-test scores. The moral outcome appeared to be 0.005 less than 0.05, showing that the direct hypothesis was plausible while the null and void hypothesis was not, proving the value of the design material.